Faculty intervention as support for first-year students (Journal of Student Affairs in Africa, 2021)
The impetus for this study is grounded in a strategic decision by management to measure readiness for university education as part of an early alert and referral system. The motivation for this project is also rooted in literature that points out that the South African higher education system faces challenges with students entering the system underprepared. Data at entry to the university, specifically related to the individual student, is used initially to profile the students. This profile is used to identify students who could be at risk of failing. These students are referred to a Faculty Student Advisor (FSA) for support to address their needs.Using a survey, 966 students were identified as being at risk at the beginning ofthe 2013 academic year. After additional criteri awere applied to our prediction model, 200 students were selected for academic development workshops or individual session provided as intervention in the first semester. An outcomes assessment method was used to determine whether the number of sessions that at-risk students attend has had an influence on their academic achievement in the first semester. The assumption is that students who made more use of the intervention services (attended more sessions) were more likely to be successful than students who defaulted on the intervention or attended fewer sessions with the FSAs.A cross-tabulation showed a significant association on the Pearson’s Chi-square statistic (13.60, df(4), p = 0.009), which implies that students who attend more sessions with the FSA are more likely to be academically successful in their first semester.
Keywords: Academic risk profile; academic success; first-year student; readiness for university